Исследование характеристик рядов ливневого стока малых рек бассейна верхнего Днестра - Киндюк, Б.В. (Культура народов Причерноморья, 2003)
У статті розглянуто питання перевірки рядів максимальних витрат води та стоку дощових паводків на однорідність та наявність різко відхиляючихся екстремальних значень за допомогою критеріїв Смирнова-Граббса та Діксона. Показано практичні розрахунки оцінки рядів зливового стоку по 19 водозборам верхнього Дністра. The article is devoted to the problem of checking the maximal flow discharge and rain discharge series influencing the uniformity and detection of abruptly raised extreme values with auxiliary of Smirnov-Grabbs and Dixon criteria. The practical results of rain discharge series evaluation for upper Dnestr 19 subwatershelds are presented.